2001
DOI: 10.1046/j.1365-8711.2001.04931.x
|View full text |Cite
|
Sign up to set email alerts
|

A possible relation between the period change and the mass ratio for W-type contact binaries

Abstract: Orbital period changes of eight W‐type contact binaries (TY Boo, BH Cas, AD Cnc, TX Cnc, RZ Com, LS Del, BB Peg and AA UMa) are presented based on the analysis of their O–C curves. It is found that the periods of the five systems TY Boo, TX Cnc, RZ Com, LS Del and AA UMa show secular increase. For BB Peg, its period increase rate has been revised. For AD Cnc, weak evidence also shows that its orbital period is increasing. For the remaining BH Cas, the three times of light minimum given by Agerer & Hubscher ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
58
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 51 publications
14
58
1
Order By: Relevance
“…Evidently, the simplistic β − q schemes seem to be insufficient in describing the short orbital evolution of a binary in which MT is not the leading evolutionary mechanism. This may be consistent with the findings of Qian (2001), who has shown that a critical value close to q cr ≈ 0.40 appears to invert the monotonicity of the observed orbital evolution in contact binaries. However, this did not emerge clearly from the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Evidently, the simplistic β − q schemes seem to be insufficient in describing the short orbital evolution of a binary in which MT is not the leading evolutionary mechanism. This may be consistent with the findings of Qian (2001), who has shown that a critical value close to q cr ≈ 0.40 appears to invert the monotonicity of the observed orbital evolution in contact binaries. However, this did not emerge clearly from the present study.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the period changes of 30 W-subtype contact binaries, Qian (2001) found that systems showing period increase usually have a higher mass ratio (q > 0.4), while the period of low-mass ratio systems (q < 0.4) show secular decreases. The conclusion was later expanded by Qian (2003) to both W-and A-subtype contact binaries who gave the relations between the period variation and the mass ratio and the orbital period.…”
Section: Discussionmentioning
confidence: 99%
“…As one can see from this table, the values of the period changes of NY Lyr are typical among the four binary stars. The recent period studies by Qian (2001aQian ( ,b, 2003 showed that the period change of W UMa-type binaries may correlate with the mass ratio of the system and with the mass of the primary component.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that orbital period changes of W UMa-type binaries are very common (e.g. Qian 2001aQian ,b, 2003. For NY Lyr, the O-C diagram published by Kreiner et al (2001) suggested that its orbital period is changeable.…”
Section: Introductionmentioning
confidence: 99%